Habituation of Qur’anic Tadarus as a Spiritual Approach to Student Discipline in Islamic Education - Mulyana Abdullah; Mintarsih Danumiharja; Hasan Sarip; Sulaiman Sulaiman; Nur Muhamad Iskandar; Ahmad Zaldi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Student discipline remains a critical issue in Islamic educational institutions, particularly as schools seek character-building strategies that move beyond external control toward internalized moral awareness. This study examines the role of Habituation of Qur’anic Tadarus (HQT) as a spiritual approach to fostering student discipline as an alternative to conventional disciplinary methods. Employing a qualitative field research design, data were collected through in-depth interviews with key informants, including the school principal, the coordinator of religious programs, and student representatives, supported by relevant documents and observations. The findings reveal that student discipline is cultivated through a structured habituation process that begins with the school bell and continues with collective Qur’anic tadarus without the use of reward-based incentives. Disciplinary outcomes are reflected in students’ punctual attendance, sustained attention during learning activities, and timely submission of assignments. The HQT program utilizes Juz 30 across all grade levels and is implemented through talaqqi-based teacher guidance, emphasizing consistency and spiritual engagement. These results indicate that spiritual habituation contributes to students’ intrinsic motivation and personal satisfaction, leading to more sustainable disciplinary behavior. This study suggests that integrating Qur’anic-based spiritual practices can strengthen character education and the development of discipline in Islamic educational contexts.